2013
DOI: 10.1521/pedi_2012_26_071
|View full text |Cite
|
Sign up to set email alerts
|

The Borderline Empathy Paradox: Evidence and Conceptual Models for Empathic Enhancements in Borderline Personality Disorder

Abstract: Empirical evidence and therapeutic interactions have suggested that individuals with borderline personality disorder (BPD) may demonstrate enhancements in aspects of social-emotional cognition. To assess the empirical evidence for this phenomenon, and to comprehensively evaluate alternative hypotheses for its possible role in BPD etiology and symptoms, the authors systematically searched the literature for investigations of empathy in BPD and reviewed 28 studies assessing a range of empathic abilities. Conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 79 publications
(111 reference statements)
0
21
0
Order By: Relevance
“…The roles of testosterone and oxytocin in other psychiatric disorders involving dysregulated social cognition, especially the major psychotic‐affective disorders schizophrenia, bipolar disorder, and depression that share symptoms and risk factors, have been less well investigated than for autism, both theoretically and empirically; indeed, conceptual, hypothetic‐deductive frameworks have yet to be developed in this context, despite the obvious importance of social hormones in human psychological phenotypes. A recently developed model for understanding the psychotic‐affective disorders, in comparison to autism, is that they involve forms of dysfunctional, ‘hyper‐developed’ social cognition, as demonstrated, for example, in such phenotypes as paranoia, other social delusions, auditory hallucination, megalomania, high levels of social emotion including guilt, shame, pride, or embarrassment, high empathic drive, and high social motivation as observed in mania (Crespi & Badcock, ; Backasch et al, ; Dinsdale & Crespi, ; Dinsdale et al, ; Sharp et al, ; Crespi & Leach, ). This model is based on the simple presumptions that evolution along the human lineage has predominantly involved increases in social cognition and emotionality (the well‐supported ‘social brain’ hypothesis) (Dunbar & Shultz, ), and that all biological phenotypes can be perturbed in two opposite directions, towards either lower or higher expression of some trait, pathway, or system, both of which cause performance deficits although by different means.…”
Section: Oxytocin Testosterone and Disorders Of Social Cognitionmentioning
confidence: 99%
“…The roles of testosterone and oxytocin in other psychiatric disorders involving dysregulated social cognition, especially the major psychotic‐affective disorders schizophrenia, bipolar disorder, and depression that share symptoms and risk factors, have been less well investigated than for autism, both theoretically and empirically; indeed, conceptual, hypothetic‐deductive frameworks have yet to be developed in this context, despite the obvious importance of social hormones in human psychological phenotypes. A recently developed model for understanding the psychotic‐affective disorders, in comparison to autism, is that they involve forms of dysfunctional, ‘hyper‐developed’ social cognition, as demonstrated, for example, in such phenotypes as paranoia, other social delusions, auditory hallucination, megalomania, high levels of social emotion including guilt, shame, pride, or embarrassment, high empathic drive, and high social motivation as observed in mania (Crespi & Badcock, ; Backasch et al, ; Dinsdale & Crespi, ; Dinsdale et al, ; Sharp et al, ; Crespi & Leach, ). This model is based on the simple presumptions that evolution along the human lineage has predominantly involved increases in social cognition and emotionality (the well‐supported ‘social brain’ hypothesis) (Dunbar & Shultz, ), and that all biological phenotypes can be perturbed in two opposite directions, towards either lower or higher expression of some trait, pathway, or system, both of which cause performance deficits although by different means.…”
Section: Oxytocin Testosterone and Disorders Of Social Cognitionmentioning
confidence: 99%
“…Nonetheless, it is easy to see why the two disorders may be considered as distinctly different from each other. The key, frequently-noted differences include the following: those diagnosed with ASPD tend to have an inflated self-image, whilst those diagnosed with BPD tend to have a negative and devalued self-image; those diagnosed with ASPD pose more of a risk to others due to their tendency towards interpersonal violence, whilst those diagnosed with BPD pose more of a risk to themselves due to their tendency to self-damaging and self-destructive behaviours; those diagnosed with ASPD tend to lack empathy and be indifferent to or contemptuous of the feelings and sufferings of others, whilst those diagnosed with BPD are likely to display reduced cognitive empathy but enhanced affective empathy (the so-called “borderline empathy paradox”) [23]. In reality, although the prototypic presentations of the two diagnoses appear to be at variance and may be almost polar opposites, the prominent symptoms appear across diagnostic groups as well as varying across time—both within and between individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Fonagy and Bateman (2019) reported that both high and low scores on RMET might suggest mentalizing deficits, thereby signaling, respectively, hypermentalizing and hypomentalizing. In fact, a number of studies (e.g., Dinsdale and Crespi, 2013) showed that individuals suffering from Borderline Personality Disorder (BPD) outperformed non-clinical individuals on RMET because of their increased proneness to focus on external features that, in the absence of genuine reflective mentalizing, makes them highly vulnerable in social contexts, generating high interpersonal hypersensitivity. In line with Fonagy and Bateman (2019), it could be argued that the absence of association between parents' and children's RMET performance emerging from our study might be attributable to a non-univocal interpretation of RMET scores, therefore, low scores, like high ones might indicate mentalizing deficits.…”
Section: Discussionmentioning
confidence: 99%